Upaya Revitalisasi Situ Di Perkotaan Suatu Tinjauan Pengelolaan Kualitas Situ Cangkring, Kota Tangerang - Bambang Priadie (JURNAL SUMBER DAYA AIR, 2011)
There has been a decreasing in the number and function of situ in the urban areas, particularly in the Greater Jakarta area, due to land use change, water pollution, as well as the growth of aquatic weeds thathave an impact on decreasing capacity of a situ as flood control. The study was conducted in Situ Cangkring, Tangerang City, consist of : bathymetry measurement, water quality, plankton, trophic status, aquatic weeds,and evaluation criteria for quality assessment of situ. Analysis method of bathymetry and morphology measurement was using Garmin 60CSx GPS with MapSource data input, calculation of water volume using the Surfer and Global Mapper, where as water quality and plankton refers to the SNI and Standard Methods. Study results: based on bathymetry map the area of Situ Cangkring was about 5.65 Ha and water volume of 108,900 m3. The area of Situ Cangkring was not decline, but there are changes in distribution and amount of aquatic weeds cover. The water quality was Class IV, diversity index of plankton was heavily polluted, dominated plankton were Chlamydomonas and Euglena; trophic status: Eutrophic Hypereutrophic.There are some water channels through into Situ Cangkring, with only one outlet. The quality value of Situ Cangkring based on computation of morphology, water quality, and aquatic weeds condition was 170. Thisvalue indicates that Situ Cangkring was disturbed lake category with recommendations need of revitalization. Suggested revitalization are : domestic waste water control in the western part, improvements of outlet channel in the northern part, and the control of aquatic weeds by mechanical and biological methods.